2017
DOI: 10.1242/jcs.200055
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of nuclear ADAR2 regulates adenosine-to-inosine RNA editing during neuronal development

Abstract: Adenosine to inosine (A-to-I) RNA editing is important for a functional brain, and most known sites that are subject to selective RNA editing have been found to result in diversified protein isoforms that are involved in neurotransmission. In the absence of the active editing enzymes ADAR1 or ADAR2 (also known as ADAR and ADARB1, respectively), mice fail to survive until adulthood. Nuclear A-to-I editing of neuronal transcripts is regulated during brain development, with low levels of editing in the embryo and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
54
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(62 citation statements)
references
References 46 publications
(67 reference statements)
6
54
0
Order By: Relevance
“…Recently, it was shown that in developing mouse neurons increased nuclear localization of ADAR2 might contribute to this phenomenon [29] together with protein modifications on ADARs and regulatory factors [30,31]. We previously showed that a gradual increase in editing is also found for filamin A, in both neuronal and non-neuronal tissues [20].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was shown that in developing mouse neurons increased nuclear localization of ADAR2 might contribute to this phenomenon [29] together with protein modifications on ADARs and regulatory factors [30,31]. We previously showed that a gradual increase in editing is also found for filamin A, in both neuronal and non-neuronal tissues [20].…”
Section: Discussionmentioning
confidence: 99%
“…The recently identified ADAR binding partners, ELAVL1, DHX9 and SRSF9 have also been shown to affect the editing level of specific sites (Aktaş et al, 2017; Huang et al, 2018; Shanmugam et al, 2018; Stellos et al, 2016). In addition to site-specific regulators of editing, Pin1, WWP2 and AIMP2 have been shown to regulate editing through post-translational modification of the ADAR proteins (Behm et al, 2017; Marcucci et al, 2011; Tan et al, 2017). However, the complexity of editing level regulation across millions of editing sites in numerous tissues and developmental stages suggests that there are likely many other proteins that regulate editing.…”
Section: Introductionmentioning
confidence: 99%
“…Loss of the ADAR2-Pin1 interaction leads to ADAR2 export into cytosol where it is ubiquitinated and degraded (32). Pin1 mediated stabilisation is important for ADAR2 editing activity during development in cortical neurons (11). However, our experiments suggest Pin1-ADAR2 interactions do not play a role in TTX up-scaling since both phosphonull and phosphomimetic mutants of ADAR2, which decrease or enhance binding to Pin1 respectively, were equally susceptible to the TTX mediated loss.…”
Section: Differential Sensitivity Of Gluk2 To Changes In Adar2 Levelsmentioning
confidence: 60%
“…ADAR2 levels are very low during embryogenesis but increase in the first postnatal week (11) to edit ~80% of GluK2, ~40% of GluK1 and ~99% of GluA2 subunits in the mature brain (12)(13)(14). ADAR2 knockout mice die at the early postnatal stage, but can be rescued by expressing the edited form of GluA2, demonstrating that unedited AMPARs are fatally excitotoxic (15).…”
Section: Introductionmentioning
confidence: 99%